A Prevalence And Nutritional Status Of Stunting Children Among 0-60 Months In Setono Pekalongan - indriyani, yulis; Teguh Irawan; Wahyuningsih, Ita; Adinda Ismail Putri; Putri Stevany Agustin; Ananda Putri Amalia; Naila Rochvika Wati; Mochammad Hilmy (Jurnal Ilmu Kesehatan, 2025)
Stunting is delayed growth due to poor health conditions or chronic malnutrition starting early in life. There are around 148.1 million cases of stunted children in various parts of the world. None other than that, Setono Pekalongan Village has the sharpest prevalence of stunting cases in 2023, reaching 120 children under five. The aim of the research is to find out the prevalence and nutritional status in cases of stunting in children aged 0-60 months. This research was a non-reactive descriptive study with total sampling involving all 66 children with stunting toddlers in Setono Village. Secondary data regarding the number of stunting cases in 2024 comes from the Sokorejo Community Health Center including variables of gender, age, weight and height. Descriptive data analysis supported by various literature studies. The results showed that 57.6% of stunted children were male, 62.1% of stunted children were aged 26-60 months, 56.1% of stunted children had normal weight and 89.4% of stunted children met the criteria according to status. Height per age in nutrition status is a short height category. It is hoped that the people of Setono will better understand the risk of stunting in their area.